Cross compliance of the Water Framework and Nitrate directives in Slovenia - Lidija GLOBEVNIK; Marina PINTAR; Urška BREMEC (Acta Agriculturae Slovenica)
We describe the first characterisation of the Slovene waters and show cross compliance of the Nitrate and Water Framework Directives in Slovenia. Point and disperse sources of pollution are identified, hydrological and morphological pressures to surface water bodies evaluated and impact of all pressure to water bodies analysed. Agricultural activities in Slovenia are described and results of calculation of nitrogen and phosphorus balance in the catchment areas of the water bodies presented. The analyses show that hydro-morphological and chemical pressures from point pressures and diffused pollution from agriculture are the main reasons for the non-attainment of environmental objectives. Though consumption of mineral fertilisers and plant nutrients in Slovenia has reached more or less steady state in the last years, the quantities are still too high to reduce the risk to water environment. Therefore, the measures for reasonable fertiliser applications should be developed into more details as to give more directions for a farm level management. Miscellaneous instruments should also be developed to initiate overall sustainable use of fertilisers and plant nutrients in agriculture.